SOME FEATURES OF LANGUAGE USE IN YORUBA TRADITIONAL MEDICINE (1991)
This study attempts to characterize some of the significant features of language form and content in texts which usually accompany the practice of Yoruba Traditional Medicine (YTM). After collection of samples of texts from different Herbalist- Client (HC) encounters in the field, some of these texts are analysed along the dimension of register studies. Those significant features which occur prominently in most of the texts analyzed are then posited as characteristic features of YTM texts. The content features of YTM texts are identified in the work by relating the texts to extralinguistic experience via the level of situation and the categories of use, function, message and structure. And the formal features are described by observing their projection of the content via grammatical and lexical options in the linguistic system. The features of situation show that these texts are products of speech events which involve human and non-human objects, Participant beliefs, actions, relations and behaviour. The texts, whose primary mode is conversational reveal especially that participants in YTM interaction believe In magical medicine, rituals and in the power of the spoken word. There are three major uses performed by YTM texts, viz. diagnosis, optional divination and medication. These uses derive from participants’ intuitive reaction to the functions and messages of the texts. The message summarizes the thematic content of each text pertaining to the identification of a problem and finding the remedy for it. And the functions provide mainly the informative and directive bases for the message content. The structure of YTM texts reveals dialogical interactions in which herbalists and clients take turns in diagnostic and prescriptive transactions to make various initiation-response moves constituted mainly by elicit-reply and direct-accept acts. In some of the texts, however, the herbalist's turns may further extend into monological transactions of divination, incantations and supplication, depending on the performance situations. Lastly, the forms of the texts show that the preponderance of some cohesive features as well as the prominence of unmarked theme and simple sentences enhance simplicity and easier comprehensibility of the messages of YTM texts. They also show that the material process and positive polarity are prominent because the texts represent a lot of physical activities carried out towards achieving a positive goal. Lastly, they show that the declarative mood marks the primary function of giving information in YTM interaction. In all, the study contributes to both Yoruba studies and text analysis in the manner in which it utilizes an eclectic textual model to explicitly analyze some texts from a Yoruba register.